Water hygiene and sanitation Best Intervention Tool for the Control of Waterborne Zoonoses - Dhaka, Pankaj; Vijay, Deepthi; Vergis, Jess; Kumar, Manesh (Indian Farming, 2015)
Universal access to improved sanitation and hygienic water sourcescould reduce diarrhoea-related deaths by more than one third of the total. Lack of clean water and a lack of basic sanitation are the undermining efforts to end extreme poverty and diseases in the world’s poor countries.